ANALISIS BIAYA OPERASIONAL KENDARAAN (BOK) DAN TINGKAT OKUPANSI ANGKUTAN TAKSI DAERAH ISTIMEWA YOGYAKARTA - Laksono, Raden Aji; Basuki, Imam; Lulie, Y. (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2015)
Abstract : Taxi’s purpose is to safety economic, comfort, swift, bring, but it is need a important factor. Such as condition of the taxi, especially their services which its important factors that user wants. One of the service task is cost, then it need controlling and accounting objective operational cost and accurate then it can use to take some decision.The purpose of this research is to analyze occupancy of the taxi’s user and yearly vehicle operating cost (VOC) for taxi. The method of the research is with in direct observation on taxi’s company and interview the owner. The vehicle operating cost (VOC) calculation using basic cost from Directorate General Of Land Transportation 2002.The result of this research is with data’s from seven taxi companys, taxi’s occupancy is 33%. According Directorate General Of Land Transportation SK.1905/KP.801/DRJD/2010 that taxi’s occupancy in DIY is less than enough, of then it services in the city need improvements. One of way to improve is using some application on such as G-maps, Ruby on Rails that combine with Android software. Average net income from seven taxi’s company by calculation is ± 80.000.000,- it’s mean that taxi’s sector is affordable to do.